History of pain theories (Storie delle teorie del dolore) - Mirko Silvestrini; Claudio A. Caputi (Publiediting, 2013)
The history of pain is as long as that of the human race. Several theories have been developed but none of them are yet exhaustive. Historically, the clinical approach has reflected the vision that society had about pain. This review analyzes the historyof pain theories through searching the literature up to the year 2013.The main source were Google Scholar and PubMed, using a numberof keywords, e.g. history of pain theories, pain, chronic pain and neuromatrix. Relevant issues were then reviewed and quoted. The authors conclude that today the notion of specific central pain region is rejected in favour of multiple neuronal networks integrated in a neuromatrix, genetically and experientially shaped. It generates the body-selfsense, which includes both pain and suffering.